Neural, psychological, and daily life evidence for a transdiagnostic process of affective dysregulation in depression and chronic widespread pain - Renz, Malika; Schmidt, Hannah; Drusko, Armin; Berhe, Oksana; Zidda, Francesca; Sebald, Carina; Andoh, Jamila; Wieland, Sebastian; Tesarz, Jonas; Treede, Rolf-Detlef; Meyer-Lindenberg, Andreas; Tost, Heike (Pain, 2025)
Chronic pain and depression are leading causes of disability, frequently co-occurring and exacerbating each other. This cross-sectional study investigated putative transdiagnostic processes of affective dysregulation in fibromyalgia (FMS) and major depressive disorder (MDD) using psychometric questionnaires (Beck Depression Inventory-II, Hospital Anxiety and Depression Scale, Cognitive Emotion Regulation Questionnaire, Perceived Stress Scale, Widespread Pain Index, Somatic Symptom Disorder B Criteria Scale 12), ecological momentary assessments, and real-time functional magnetic resonance imaging amygdala neurofeedback during an emotion regulation task. We compared clinical symptoms, stress sensitivity, and emotion regulation in patients with FMS (N = 46) and MDD (N = 48) with healthy controls (N = 34). Patients with fibromyalgia syndrome and major depressive disorder reported similar psychopathological and affective dysregulation profiles, and they exhibited more psychopathology and emotion regulation deficits than healthy controls (HC). Differences between MDD and FMS were limited to pain-specific pathology in FMS (pain spread and frequency P < 0.001, intensity P < 0.05) and more rumination (P < 0.05) and self-blame (P < 0.01) in MDD. Momentary stress predicted higher subsequent pain and worse affective states across groups, with FMS and MDD exhibiting stronger stress responses (all P's < 0.05). Directly after neurofeedback training, FMS and MDD were less able to downregulate left amygdala activity than HC (P = 0.039) compared to baseline performance, and this brain marker predicted daily life psychopathology (negative affect, anxiety, and rumination, all P's < 0.05). Patients with fibromyalgia syndrome additionally exhibited unique deficits in right amygdala regulation (P = 0.004). Our findings highlight transdiagnostic affective dysregulation patterns in FMS and MDD, specific differences in emotion regulation strategies, and a potential neuronal marker of a shift towards right amygdala sensitization during affective processing in FMS.
Gesehen am 15.01.2026